Adjustment of segmental rotations to achieve both racket speed and accuracy at various impact heights during a two-handed backhand stroke - Zhang, S.; Sado, N.; Fujii, N. (Sports Biomechanics, 2025)
This study investigated the influence of impact height and competitive level on racket speed and stroke accuracy by analysing segmental angular kinematics under a random ball condition. High- (HQ, n = 7) and low-quality (LQ, n = 7) groups were determined by k-means clustering of the ratio of ball landing in the target (accuracy) and racket speed decrease. HQ showed higher accuracy (48.3% vs. 32.4%), less speed decrease at lower impact heights (-4.4% vs. -10.3%) and better competitive level ranking [median (1st-3rd quartiles); 4 (2-7)] than LQ [10 (8-13)]. HQ produced greater racket speed (24.4 vs. 21.6 m/s), especially with a notable horizontal velocity (23.8 vs. 20.8 m/s) of the racket at lower impact height, which was attributed to the central role of greater angular velocity of pelvis and thorax in the hitting direction. Both groups showed similar adjustment mechanisms that due to the decrease in angular velocity of pelvis, players increased the relative rotation angle between pelvis and thorax to maintain angular velocity of thorax when transitioning from low to high impact heights. Our findings suggest that players should emphasise the coordination between pelvic and thoracic rotations according to impact heights to maintain racket speed while controlling ball landing position.